2000
DOI: 10.1128/mcb.20.19.7170-7177.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activation of V(D)J Recombination Induces the Formation of Interlocus Joints and Hybrid Joints in scid Pre-B-Cell Lines

Abstract: V(D)J recombination is the mechanism by which antigen receptor genes are assembled. The site-specific cleavage mediated by RAG1 and RAG2 proteins generates two types of double-strand DNA breaks: blunt signal ends and covalently sealed hairpin coding ends. Although these DNA breaks are mainly resolved into coding joints and signal joints, they can participate in a nonstandard joining process, forming hybrid and open/shut joints that link coding ends to signal ends. In addition, the broken DNA molecules excised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…As shown in Figure 2B, both SEs and SJs made in Sp9 are sensitive to ApaL1 digestion, indicating the presence of intact SEs and précised joining of these ends in wild-type cells. On the other hand, S9 cells produce intact SEs but imperfect SJs (because of incomplete ApaL1 digestion), which results from their partial abnormality in SJ formation, as reported previously (Lew et al, 2000). In contrast, the integrity of SEs and SJs recovered from zebrafish samples was found inverse to those made in S9 cells, i.e.…”
Section: Aberrant Signal Ends and Précise Signal Joints In Zebrafish supporting
confidence: 78%
“…As shown in Figure 2B, both SEs and SJs made in Sp9 are sensitive to ApaL1 digestion, indicating the presence of intact SEs and précised joining of these ends in wild-type cells. On the other hand, S9 cells produce intact SEs but imperfect SJs (because of incomplete ApaL1 digestion), which results from their partial abnormality in SJ formation, as reported previously (Lew et al, 2000). In contrast, the integrity of SEs and SJs recovered from zebrafish samples was found inverse to those made in S9 cells, i.e.…”
Section: Aberrant Signal Ends and Précise Signal Joints In Zebrafish supporting
confidence: 78%
“…Lew et al (2000) have demonstrated that severe combined immude deficiency (scid)-homozygous (s/s-ts) pre-B-cell lines transformed with a temperature-sensitive Abelson murine leukemia virus mutant (ts-Ab-MLV) produced high levels of hybrid joints, exceeding that of its scid-heterozygous (s/ϩ-ts) counterparts expressing functional DNA-PKcs. The s/ϩ-ts cells mostly produced hybrid joints with an intact RSS and coding sequence, while the s/s-ts cells exhibited hybrid joints with extensive nucleotide deletions in both the RSS and the coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that RAGs, HMGB1, DNAPKcs, Ku70, and Ku80 form a pre-cleavage complex on the RSS. This explains the high incidence of non-standard [44,45,52,53,80] and interlocus joints [54,81] formed in scid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The scid mutation is mapped to the gene encoding the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs) [49][50][51]. Scid cells exhibit a high frequency of non-standard junction formation [52][53][54] and thus, are useful for detection of nonstandard junctions in our assays. Our results indicate that murine pre-B cell do not prefer the wild-type 12 bp RSS in the deletional orientation over the inversional orientation.…”
Section: Introductionmentioning
confidence: 99%